ANALISIS KINERJA COOLANT PADA RADIATOR - Alexander Clifford; Riza Abrar; Steven Darmawan (Jurnal Ilmiah Teknik Mesin POROS, 2014)
Abstract: This research learn about characteristic of radiator coolant effectiveness, which are influenced by flow rate, density, and fluid viscosity. Experimental method is used to get parameters: such as coolant temperature, air temperature and flow rate. This study use ɛ-NTU method to analyze the data. The results of coolant A, B, and water have effectiveness of 40%, 37%, and 36% respectively, it is caused by coolant A have the biggest Universal coefficient number and convection coefficient number are compared with coolant B and water.